The Current Status of the Preclusive Effects of Judgments in the Federal Court System of the United States of America - Heller, Thomas Allan (Collected Papers of Thomas A. Heller, 2025)
Res judicata law in the United States of America has a long, extensive and complex history. The aim of this paper is to provide at least a working summary of some of the most important aspects of the current res judicata law in the federal court system of the United States. The flexible discovery, pleading and joinder rules have given rise to more expansive res judicata law. The paper will discuss what exactly constitutes a judgment; how the federal courts deal with finality of judgments in multiple party and multiple claim cases; the final judgment rule; the form of judgments; the methods to enter judgments and significance of entry of judgments; together with a detailed overview of the doctrine of res judicata itself, including the separate, but related twin doctrines of claim preclusion and issue preclusion.